Synergized security framework: revolutionizing wireless sensor networks through comparative methodological analysis - Guodong Su; Boliang Zhang (Scientific Reports)
Abstract Wireless Sensor Networks (WSNs) are increasingly deployed in critical applications from healthcare to military systems, yet they face significant security challenges due to their resource constraints and distributed nature. This paper addresses two fundamental security problems in WSNs, i.e., vulnerable key distribution and Sybil attacks. Specifically, we propose a synergized security framework, a groundbreaking approach tailored to enhance the security performance of WSNs. First, a bidirectional hash-based key pre-distribution scheme that increases key generation complexity by 43% while maintaining low memory requirements. Second, a multi-trust layered detection mechanism that combines energy consumption pattern analysis with fuzzy logic for Sybil attack detection, achieving a 91.7% detection rate. Finally, comprehensive evaluations using OMNeT++ with networks of 1–500 nodes demonstrate that our framework outperforms existing protocols (LEAP, SPINS, ESK) by 17–32% in network throughput and 12–26% in node connectivity, while maintaining comparable latency to quantum-based methods (QKD, BB84). Real-world validation in a 32-node test environment confirms the framework’s practical effectiveness with only 4.3% performance deviation from simulation results. Our framework particularly excels in dynamic networks, maintaining 89% effectiveness even with 15% node mobility rates, significantly advancing the state-of-the-art in WSN security.